UPAYA MENINGKATKAN PRODUKSI PADI (Orhyza Sativa L) DENGAN PENGATURAN MODEL TANAM JAJAR LEGOWO - Fauzia Hulopi; Sutoyo Sutoyo (BUANA SAINS, 2010)
Efforts to increase rice production, such as setting planting legowo row model. Objective: to study the model settings legowo row planting in rice. The experiment was conducted in paddy fields in the Village District Pulongdowo Tumpang Malang. The research location is situated at an altitude +597 m asl, alluvial soils with a temperature between 22o-30oC and average rainfall is 2113 mm.year-1. The experiment was conducted in April-July 2009. Experiments using a Randomized Complete Block Design Factorial with repeated 5 times. Treatment plant model consists of 5 types, namely 1 = square, 2 = rectangle, 3 = legowo row 2:0, 4 = legowo row 4:0, and 5 = legowo row 8:0. The data obtained were tested LSD 1%. Results showed the treatment of square, rectangle and parallelogram legowo 2:0 high yield crops and productive tillers were not significantly different. Likewise, treatment of legowo row 4:0 and 8:0 high crop yield and productive tillers were not significantly different. Treatment of square, rectangle and parallelogram legowo 2:0 flowering earlier than treatment legowo row 4:0 and 8:0. Treatment of legowo row 4:0 and 8:0 produce dry grain harvests each 9:17 ton.ha-1 and 9:04 ton.ha-1 the highest and different compared to other treatments. Treatment of squares and rectangles to produce dried grain harvest 8:02 ton.ha-1 and 7.95 ton.ha-1 respectively but lower and different from other treatments